Analisis Terkait Justice Collaborator Sebagai Faktor Yang Meringankan Sanksi Pidana Richard Eliezer - Dena Aji; Aditya Tampubolon; Halimah Citra; Rizky Bayu; Herli Antoni (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The focus of this research is the factors that might be considered by judges when granting criminal sanction relief to a Justice Collaborator. Second, how does the application of Justice Collaborator affect criminal cases in Indonesia and what are the impacts. In this study, the approach method used is normative juridical research method. The results of the study show that there are several regulations in Indonesia that regulate Justice Collaborators in the criminal justice system, but they have not been regulated in detail in the Criminal Procedure Code. Justice Collaborators have an important existence and urgency in the criminal justice system, especially in the stages of investigation, examination, prosecution and execution of decisions.